The Essence of Citizenship Education in Elementary Schools - Muhammad Rusli; Maya (CV. Kalimasada Group Profesional, 2023)
Every individual or every citizen is expected to be able to live a life of benefit to the nation and state and be able to anticipate developments and changes in the future. For this reason, provision of science, technology and art is needed which is based on religious values, moral values and national cultural values. These basic values are used as role models and life guidelines for every citizen in the life of society, nation and state. One of the learning contents that concerns understanding the unity and awareness of citizens in a country is citizenship education. Comprehensively, this article will discuss the concept, nature and existence of citizenship education learning, especially in elementary schools through literature studies. Literature studies are carried out by analyzing and generalizing various theories that are relevant to the problem being studied as material for developing concepts according to what is being studied. Researchers reveal that citizenship education is a subject that focuses on the formation of citizens who understand and are able to carry out their rights and obligations to become Indonesian citizens who are intelligent, skilled and have character as mandated by Pancasila and UUD1945. In general, citizenship education is a very important subject. important. for students, it has visible characteristics from objects, scope of material, learning strategies, to the final goal of this education.